Um curso básico de astronomia - Nobre Júnior, Abelardo Pedro (2020)
This work aims to disseminate Astronomy in a scientific way in an interdisciplinary and motivating perspective for science as a whole, using as a dissemination tool a basic Astronomy course offered to teachers of the most diverse disciplines of basic education and to students of elementary education and schools located in the municipality of Murici, located in the forest area of ​​the State of Alagoas. This course was offered to the community in a class of an average of 25 students over a period of four days with a total workload of 20 (twenty) hours of classes, of which 12 (fifteen) are theoretical, covering: the history of Astronomy, the celestial sphere, the celestial movements, the stars, the constellations, the galaxies and the solar system with all its members, that is, the Sun, the planets, the dwarf planets, the comets, the asteroids, the moons and other stars of our system. The remaining 08 (eight) hours constituted observations and, to this end, a 50mm telescope of the GREIKA brand and the stellarium program were used, given the nature of astronomical science itself, which provides different environments for its learning, that is, the classroom environment and the external environment for sky observations. Two educational products were generated, one, the basic course in Astronomy that can be offered in other schools and Institutes as a form of training for teachers of different levels of education or just as a tool for the dissemination of Astronomy and, the other, Educa Space; a didactic game that aims to evaluate the contents taught in the course or be a playful working tool for the classroom. The objective of the course was achieved, that is, to enable the participants to awaken a greater interest in science, as well as to contribute to intellectual enrichment, providing each participant with the possibility of becoming a multiplier of astronomical and scientific dissemination.